The Role of The Financial Audit Report on the Decision-Making In the Economic Institution An analytical study of SONATRACH - RAMDANI , Afif; MEKID , Ali (Journal of Research in Finance and Accounting, 2022)
Introduction: This study aims to analyze and determine the role of the financial audit report on decision-making in SONATRACH. Hence, it focuses on using different models and tools to ensure hypotheses test and purposes achievement. Results: Findings show that the financial audit report is financial information that has quality. Moreover, the financial audit impacts the integrity and equity of the financial situation; Therefore, its role is to support the board of directors to control the financial performance, keep up, and improve institutional purposes and activities. Discussion: Through the analysis of the financial and administrative activities and performance, the financial audit report is a reliable indicator in decision-making in SONATRACH from the perspective of support, confirmation, and evaluation.